Perspektif Ekonomi Islam Terhadap Pendistribusian Zakat Di Baznas Karangasem Bali - Fitri Amalia; Nanda Hidayan Sono (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
Zakat distribution is the distribution, distribution, delivery of goods or services to many people or several places. The distribution of zakat has clear and directed targets and objectives according to the basis stated in the Al-Qur'an which is applied to the form of zakat distribution. The method used in this research is a descriptive method using a qualitative approach which aims to describe zakat institutions in a comprehensive and comprehensive manner through observation, interviews and documentation. The results of this research explain that the forms of distribution of zakat funds carried out by zakat institutions to improve community welfare are consumptive distribution and productive distribution so that they are able to improve people's living standards. The targets of zakat distribution carried out by BAZNAS Karangasem Bali are eight asnaf, namely the needy, poor, amil, converts, riqab, gharimin, fisabilillah, and ibn sabil. The steps for distributing zakat carried out by BAZNAS Karangasem Bali are planning, implementation and supervision. So, with distribution in the form of empowerment and the right targets and good stages at BAZNAS Karangasem Bali, it has succeeded in improving the welfare of the community.